Transformation ratio at wakefield acceleration in dielectric resonator - Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2014)
The expressions for the wakefield have been derived and it has been shown that the transformation ratio in the
dielectric resonator is significantly higher than the transformation ratio in the case of waveguide at large number
of injected trains of identical bunches. Получены выражения для кильватерного поля и показано, что коэффициент трансформации в диэлектрическом резонаторе значительно превышает его в случае волновода при значительном количестве инжектированных профилированных цугов одинаковых сгустков. Отримано вирази для кільватерного поля і показано, що коефіцієнт трансформації в діелектричному резонаторі значно перевищує його у випадку хвилеводу при значній кількості інжектованих профільованих цугів однакових згустків.